PTH-215 Trace elements and vitamin levels in long-term home parenteral nutrition paediatric patients. (22nd June 2015) - Núñez-Ramos, R; Gallego, S; Gayda-Pimlott, D; Macdonald, S; Koeglmeier, J; Hill, S
Abstract : Introduction: Parenteral Nutrition (PN) is lifesaving therapy for children with intestinal failure (IF). Long-term home PN patients depend on commercially prepared intravenous multivitamin and trace element (TE) formulations. Patients should have regular assessment of micronutrient and vitamin status to avoid deficiencies. Our aim is to analyse micronutrient levels in our home PN cohort. Method: We performed a retrospective review including children with IF who had been on home PN for at least 1 year. Demographic and clinical data were collected, including serum concentration of copper, selenium, iron, zinc, vitamin A, E, D, B12, folate and ferritin. Patients were categorised as deficient or normal, based on the mean value assessed in the last 6 months. Deficiencies were defined according to our laboratory reference range. The most commonly used TE, fat-soluble vitamins and water-soluble vitamins supplementation formulations were Peditrace®, Vitalipid® and Solivito®, prescribed according to ESPGHAN 1 guidelines, with adjustments as needed depending on each patient's requirement. Micronutrient enteral supplementation was also recorded. Results: 30 patients (16 male), median age 7.65 years (2.18–16.71), were included. The indications for home PN were gastrointestinal motility disorders (11 patients), short bowel syndrome (SBS, 8 cases), congenital enteropathies (6 cases), eosinophilic enteropathies (3 cases) and protein-losing enteropathy (2 cases). Median time on home PN was 3.85 years (0.67–12.08), ranging from 2 to 7 days a week, ussually infused over 12 h overnight. Twenty-two patients (73.3%) had at least one TE deficiency, 43.3% (13 patients) had at least one vitamin deficiency, and 26.7% (8 patients) had multiple micronutrient dificiencies. The most common micronutrient deficiencies identified were copper (46.7%), vitamin A (43.3%), selenium (20%), ferritin (20%) and zinc (10%). The higher rates of TE deficiencies were found among patientes with diagnosis of congenital enteropathies (83.3%) and SBS (75%). No morbidity associated with these deficiencies was observed. Vitamin E, D, B12 and folate levels were all normal. Eight patients were receiving enteral vitamin supplementation in addition to PN vitamins. Conclusion: Although laboratory results outside the normal range were common in children with IF on home PN, there were no significant clinical abnormalities. The most frequent findings were suboptimal copper, vitamin A, selenium and ferritin levels. Our results emphasise the critical importance of routine surveillance of TE and vitamin levels and the need to prescribe home PN according to individual requirements. Disclosure of interest: None Declared. Reference: Koletzko B, et al . Pediatr Gastroenterol Nutr. 2005;41